(untitled) (Al-Farooq Journal of Sciences, 2026)
Interior design plays a crucial role in shaping the indoor environment, inevitably impacting its occupants—whether positively or negatively—by influencing their comfort, tranquility, and mood. Residential interior design is defined as the process of planning and analyzing interior spaces to devise optimal solutions regarding circulation, furniture layout, the selection of materials, colors, and lighting, and more. It employs innovative approaches to create a suitable environment that fosters comfort and happiness for residents, serving as a discipline that caters to every individual, regardless of their health, social, or financial status. Interior design serves not only to create a comfortable environment for general users; its role becomes far more critical and profound when addressing the needs of individuals with special requirements—particularly children with autism. These children often struggle to adapt to their home environments, exhibiting aggressive behaviors that can endanger themselves or those around them. This situation places immense psychological strain on parents, turning daily life into a constant battle to manage the child’s behavior and gain their cooperation. The research addresses the potential of utilizing residential interior design to accommodate these children’s cognitive and sensory needs while helping to soothe their behavior. Ultimately, the study aims to create an environment that fosters their adaptability, self-reliance, and social integration, thereby alleviating the burden of total responsibility shouldered by their families. This descriptive study concludes that interior design can contribute positively and effectively to alleviating negative behavioral symptoms in individuals with autism and highlights the feasibility of implementing specific design principles for the residential environments of children across the autism spectrum. The study recommends encouraging interior designers to prioritize design considerations tailored to children with autism—ensuring that focus is not limited to learning environments while neglecting residential spaces—and advocates for incorporating behavioral theories into the design theory curricula for art and interior design students at local universities.